Short Historical Summary of Roads in Colombia - Osorio Baquero, Ismael (Ingeniería Solidaria, 2014)
Pre-Columbian indigenous peoples developed a variable degree of capacity to undertake and execute road works. Their most important abilities involved building diverse types of bridges and boats. Paths that run in a straight line, no matter the incline, stem from the need to arrive at a certain place as soon as possible; because they were physicallyfit walkers, inclines were no obstacle. In the past, there were paths. Thepre-Columbians traveled over them to trade and “barter” more than in an attempt to impose a shared language. Because they had developed their civilizations in the mountain ranges, their artistry in building trails and bridges, reaching distant markets by climbing mountains and crossing rivers led them to create bridges using vines, to build stone pathways and stairs as perfect as those of the Taironas, and to cross provinces with diverse languages such as the royal pathways used by the Inca chasquis (messengers) when traveling between farms at the speed of mules, which also happened among the Aztecs.
Keywords: pre Columbian paths; national roads; railways; Colombia